Morphological response of the larvae of Arbacia lixula to near-future ocean warming and acidification - Visconti, G; GIANGUZZA, Fabrizio; Butera, E; Costa, V; VIZZINI, Salvatrice; Byrne, M; GIANGUZZA, Paola (ICES Journal of Marine Science, 2017)
The distribution of the sea urchin Arbacia lixula, a warm affinity species, has been expanding in the Mediterranean Sea. To address questions on potential for future success of this species in the region, the thermo-tolerance of larval development was investigated in context of regional warming. The larvae were reared in present day spawning period (20°C) and warming conditions (+4 = 24 and +6 = 26°C). As the calcifying larvae of sea urchins are vulnerable to stunted growth caused by ocean acidification, the impact of lower pH (-0.3 pH units) on larval development was also investigated in combination with warming. Morphological traits of the larvae, post-oral length arms, overall length of larvae and body length, were affected by increased temperature across pH treatments, indicating that 24°C was optimum for development. A slightly negative effect of pH was evident. Increased temperature ameliorated the stunting effect of acidification on growth. The thermal tolerance of A. lixula development overlaps with projections for warming in the region by 2100 and also indicates that this species has acclimatized or adapted its reproductive biology to the broad environmental conditions of the Mediterranean Sea. Due to the broad thermal range (~ 10 °C) of development of A. lixula across its distribution, this species is likely to be a winner in the climate change stakes. The broad thermal tolerance of the larvae is likely to assure population connectivity between Mediterranean sub-basins populations. The continued success of A. lixula could be have a strong consequences for the ecological structure of Mediterranean rocky habitat.